Ijtihad Metodologis dan Agenda Reformasi Syari’ah Abdullahi Ahmed An-Na’im - Zuhri Humaidi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
One of the central themes within contemporary Islamic thought is the reform of Islamic law (Sharia). As posited by An-Na’im, the implementation of Sharia in the modern era is confronted with profound epistemological and axiological dilemmas. On the one hand, there is a persistent and strong motivation among Muslims to implement Sharia as an operational public law. On the other hand, traditional Sharia formulations exhibit inherent contradictions with modern public law frameworks, specifically regarding constitutionalism, criminal law, international law, and human rights. This article aims to analyze the methodological frameworks and Sharia reform proposals conceived by An-Na’im as a resolution to these contradictions. The discussion also evaluates the enduring relevance of his ideas for further development within an ever-evolving global context. To achieve this, the analysis employs a descriptive-analytical and hermeneutic approach. The findings demonstrate that: First, An-Na’im reconstructs the classical theory of abrogation (naskh) into a new paradigm termed ‘reversed naskh’. This theory privileges Meccan verses as the foundational core because they embody the values of liberty, equality, modern ethics, and respect for human rights. Second, his Sharia reform addresses several critical areas, including gender relations, interreligious dynamics, criminal law, jihad, and slavery. Third, An-Na’im’s conceptual framework demands continuous expansion and contextualization to address contemporary, emerging issues